Decoding the Prognostic Significance of Lymphadenectomy Extent in Esophageal Cancer: A Navigational Study - Sait Zafer Ferahköşe; Ramazan Kozan; Murat Akın (Gazi Medical Journal)
Objective: Esophageal cancer lacks a standard surgical approach, and opinions differ regarding the extent of lymphadenectomy. This study aimed to assess the correlation between the extent of lymphadenectomy, patient and tumor characteristics, and survival of esophageal cancer. Methods: Data of 101 patients who underwent surgery for esophageal cancer between 1990 and 2022 were retrospectively analyzed. The mean survival and 1, 3, 5, and 10 year overall survival (OS) rates were examined. Overall survival rates for adenocarcinoma and squamous cell carcinoma were separately evaluated. The relationships among gender, age, tumor size, stage, total number of harvested lymph nodes, and survival were analyzed. Results: Among 101 patients, 34 (33.7%) were female, and 67 (66.3%) were male, with a mean age of 61.01±12.01 years. Among the included patients, 82 (81.2%) had squamous cell carcinoma and 16 (15.8%) had adenocarcinoma. The mean follow-up was 61.2 months, and the OS averaged 61.01±12.01 months. Only the total harvested lymph node count had a statistically significant impact on survival (p=0.17). Conclusion: There was a clear association between the total number of harvested lymph nodes and OS. In squamous cell cancers, the extent of lymph node dissection improves long-term survival. However, the routine use of extended lymphadenectomy for distal cancer remains a topic of debate.